Menggali Fungsi dan Makna Bale Gading dalam Upacara Dewa Yadjna: Kajian Bentuk, Fungsi, dan Makna - Widyawati, Anak Agung Ayu Alit; Gaduh, Acyutananda Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Hindus in Bali in carrying out the yajna ceremony still adhere to the teachings passed down by their ancestors and sometimes do not know the function and meaning of the ceremony. This is starting to be shaken by the critical minds of the younger generation who are starting to question why a ceremony is being carried out, therefore this research was conducted to discuss one of the types of ceremonies used in a yajna ceremony, namely the use of ivory bale in the god yajna ceremony. The form, function and meaning of using the ivory bale in the Dewa Yajna ceremony was studied using a qualitative descriptive method in which data were obtained from observation, document studies and interviews. The discussion begins with the definition and mythology of the ivory bale. Bale ivory is a small white and yellow bale whose function is to honor Sang Hyang Semara Ratih and has theological meaning, sociological meaning and ethical or ethical meaning in living life.